2022
DOI: 10.1088/1755-1315/1024/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life Estimation of Mocaf Dry Noodles Using Critical Moisture Content Approach in Various Packaging

Abstract: This study aims to determine the critical moisture content, moisture sorption isotherm (MSI) curve and the shelf-life of mocaf dry noodles products using the Accelerated Shelf-Life Testing (ASLT) approach to the critical moisture content approach using two types of packaging, PP (Polypropylene) and metalized. The results of this study are obtained critical moisture content of mocaf dry noodles products of 15.8467% (db), with the MSI curve at 30°C forming a type II isotherm type sigmoid curve with the equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…A disaster condition requires the stockpiled rations to be shelf‐stable for an extended period compared to routine food products. Several studies have been dedicated to evaluating the best means of accelerated shelf‐life stability calculation (Bharath Kumar & Prabhasankar, 2018; Byun et al., 2010; Darsch & Moody, 2009; Ekafitri et al., 2021; González et al., 2017; Khan et al., 2014; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009; Tuersuntuoheti et al., 2019; Yang et al., 1997; Zhang et al., 2016). Researches have shown that water activity has been among the most preferred methods of shelf‐life estimation for noodles and similar products (Li et al., 2011; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A disaster condition requires the stockpiled rations to be shelf‐stable for an extended period compared to routine food products. Several studies have been dedicated to evaluating the best means of accelerated shelf‐life stability calculation (Bharath Kumar & Prabhasankar, 2018; Byun et al., 2010; Darsch & Moody, 2009; Ekafitri et al., 2021; González et al., 2017; Khan et al., 2014; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009; Tuersuntuoheti et al., 2019; Yang et al., 1997; Zhang et al., 2016). Researches have shown that water activity has been among the most preferred methods of shelf‐life estimation for noodles and similar products (Li et al., 2011; Mitrevski et al., 2016; Putri et al., 2021; Sefrienda et al., 2022; Sirpatrawan, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the method used by Sefrienda et al. ( 2022 ), organoleptic tests were also used in the shelf‐life determination of the noodles, as well as the water activity‐based method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations